Camrelizumab Combined with FOLFOX4 Regimen as First-Line Therapy for Advanced Hepatocellular Carcinomas: A Sub-Cohort of a Multicenter Phase Ib/II Study - Li H; Qin S; Liu Y; Chen Z; Ren Z; Xiong J; Meng Z; Zhang X; Wang L; Zhang X; Zou J (Dove Medical Press, 2021)
Hui Li,1,* Shukui Qin,1,* Ying Liu,2 Zhendong Chen,3 Zhenggang Ren,4 Jianping Xiong,5 Zhiqiang Meng,6 Xiao Zhang,7 Linna Wang,7 Xiaojing Zhang,7 Jianjun Zou7 1Department of Medical Oncology Center, Bayi Affiliated Hospital, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 2Department of Oncology, Cancer Hospital of Henan Province, Zhengzhou, People’s Republic of China; 3Department of Clinical Oncology, The Second Affiliated Hospital of Anhui Medical University, Hefei, People’s Republic of China; 4Department of Clinical Oncology, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 5Department of Clinical Oncology, The First Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 6Minimally Invasive Treatment Center, Fudan University Shanghai Cancer Center, Shanghai, People’s Republic of China; 7Jiangsu Hengrui Medicine Co., Ltd, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shukui QinDepartment of Medical Oncology Center, Bayi Affiliated Hospital, Nanjing University of Chinese Medicine, No. 34, 34 Biao, Yanggongjing Street, Nanjing, 210002, People’s Republic of ChinaTel + 86-25-80864541Email qinsk@csco.org.cnBackground: Immune checkpoint inhibitors and chemotherapy can synergistically increase efficacy in a variety of malignancies. We conducted this phase Ib/II study to assess the safety and efficacy of anti-PD-1 antibody camrelizumab in combination with FOLFOX4 for treatment-naive advanced hepatocellular carcinoma (aHCC).Methods: This open-label, multicenter phase Ib/II study (NCT03092895) enrolled patients with aHCC and without prior systemic treatment for treatment with camrelizumab (3 mg/kg) and FOLFOX4 every two weeks. First, six patients were enrolled, followed by an additional 28 patients after dose-limiting toxicity cases were determined to be < 33% of patients. The primary endpoint was tolerability and safety of treatment.Results: A total of 34 aHCC patients were enrolled and received study treatment. No dose-limiting toxicity were observed in the first six patients enrolled. Twenty-nine (85.3%) of the total 34 patients had grade ≥ 3 treatment-related adverse events (TRAEs), with the most common ones being decreased neutrophil count (55.9%) and decreased white blood cell count (38.2%). No TRAEs-related deaths occurred. The objective response and disease control rate were 29.4% (95% CI, 15.1– 47.5) and 79.4% (95% CI, 62.1– 91.3), respectively. The median duration of response, progression-free survival, and overall survival was 6.9 months (range, 3.3– 11.5), 7.4 months (95% CI, 3.9– 9.2), and 11.7 months (95% CI, 8.2– 22.0), respectively.Conclusion: Camrelizumab combined with FOLFOX4 for first-line treatment of patients with aHCC showed good safety and tolerability, with promising preliminary antitumor activity.Keywords: PD-1 monoclonal antibody, camrelizumab, FOLFOX4 regimen, hepatocellular carcinoma, combination therapy